Soil fertility status of the rice and maize growing soils of Vikarabad district of Telangana - P. SURENDRA BABU; D. SREELATHA, B. POOJA, M. CHANDINI PATNAIK (The Journal of Research, PJTSAU, 2026)
The investigation was conducted at ARI, Ranjendranagar, to know the soil fertility status of the rice and maize growing soils of Vikarabad, Ranga Reddy and Yadadri district of Telangana. Soil samples were collected by random sampling method and soils were analyzed for their fertility status. In paddy grown soils, the pH, electrical conductivity, and organic carbon ranged from 6.06 to 8.08, 0.03 to 0.62 dS m-1 and 0.12 to 1.28 percent and in maize grown soils ranged from 5.31 to 7.94, 0.02 to 0.37 dS m-1 and 0.12 to 1.26 %, respectively. The paddy soils were very low to medium in available nitrogen, low to very high in available phosphorus, low to high in available potassium. The maize soils were very low to medium in nitrogen content, medium to very high in available phosphorus, low to high in available potassium. Paddy and maize soils were deficient in zinc to an extent of 20 and 37 %.